Multi-agent systems for education and interactive entertainment design, use and experience - Beer, M. D. (Martin D.); Fasli, Maria; Richards, Debbie; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book presents readers with a rich collection of ideas from researchers who are exploring the complex tradeoffs that must be made in designing agent systems for education and interactive entertainment"--Provided by publisher.
1. MAgICS / Forrest Stonedahl, Michelle Wilkerson-Jerde, Uri Wilensky -- 2. An intelligent agents and multi-agent systems course involving NetLogo / Ilias Sakellariou, Petros Kefalas, Ioanna Stamatopoulou -- 3. Adapting rewards to encourage creativity / F. Grove ... [et al.] -- 4. A Multiagent approach to teaching complex systems development / Simon Lynch, Keerthi Rajendran -- 5. Introducing AI and IA into a non computer science graduate programme / Ioanna Stamatopoulou, Maria Fasli, Petros Kefalas -- 6. Introducing multiagent systems to undergraduates through games and chocolate / Emma Bowring, Milind Tambe -- 7. Survey of educational multi-user virtual environments and agents / Arda Tezcan, Debbie Richards -- 8. A Comparative study of platforms for multi-user virtual environments / Arda Tezcan, Debbie Richards -- 9. Agents with a theory of mind in virtual training / Maaike Harbers, Karel van den Bosch, John-Jules Meyer -- 10. Computers can feel too / K. Chatzara, C. Karagiannidis, D. Stamatis -- 11. Scenario authoring by domain trainers / Debbie Richards, Meredith Taylor -- 12. Crafting a personalised agent-oriented mobile E-learning platform for adaptive third level education / Olapeju Ayoola, Eleni Phelan -- 13. How to build up recommender agents, step by step / Josep Lluis de la Rosa ... [et al.].
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed Jan. 13, 2011).
Keywords: Multiagent systems -- Congresses; Instructional systems -- Congresses; Computer science -- Study and teaching -- Congresses; E-learning platforms; Intelligent emotional agents in e-learning systems; Virtual training; Recommender agents; Multiagent systems; Teaching AI and IA; Complex systems development; NetLogo; Multi-user virtual environments and agents; Agent-based modeling; Domain trainers; (Immersive) virtual reality/environment; Case-based reasoning; Cognitive, emotion and personality modelling; Embodied agents; Game development; Human computer interaction; Knowledge acquisition; Knowledge based reasoning; Language technology including speech, linguistics, dialogue; Multi-agent environments and social systems; Scenario analysis; Storytelling/narrative engines; User modelling; Electronic books